Phosphodiesterase-4 Inhibitors for Non-COPD Respiratory Diseases - Kawamatawong, Theerasuk (Frontiers in Pharmacology, 2021)
Selective phosphodiesterase (PDE) inhibitor is a class of non-steroid anti-inflammatory drugs for treating chronic inflammatory diseases. Modulation of systemic and airway inflammation is their pivotal mechanisms of action. Furthermore, PDE inhibitors modulate cough reflex and inhibit airway mucus secretion. Roflumilast, a selective PDE4 inhibitor, has been extensively studied the efficacy and the safety in COPD patients. According to the mechanisms of action, the potential roles of PDE inhibitors for treating chronic respiratory diseases including severe asthma, asthma COPD overlap (ACO) non-cystic fibrosis (CF) bronchiectasis, and chronic cough are discussed. Since roflumilast inhibits airway eosinophilia and neutrophilia in COPD patients. Hence It reduces COPD exacerbations in the presence of chronic bronchitis in addition to baseline therapies. The clinical studies in asthma patients have shown the comparable efficacy of roflumilast to ICS for improving lung function. The ongoing clinical trials of roflumilast in severe asthma have been limited. Despite asthma and COPD overlap (ACO) is common and is also associated with poor outcome. There is no clinical trial regarding its efficacy in patients with ACO despite its promising role in reducing COPD exacerbation. Since mucus hypersecretion is a result of neutrophil secretagogue in patients with chronic bronchitis. PDE4s are regulators of cystic fibrosis transmembrane conductance regulator (CFTR) in human airway epithelial cells. In addition, goblet cell hyperplasia is associated with an increased expression of PDE. Bronchiectasis and chronic bronchitis are neutrophilic airway disease presenting with mucus hypersecretion. They are commonly coexisted and leading to severe disease. The role of PDE4 inhibitor, roflumilast, in non-cystic fibrosis bronchiectasis is under investigation in clinical trials. Lastly, PDE inhibitors have been shown modulating cough from bronchodilation, suppression of transient receptors potential vanilloid (TRPV1 and TRPV4) and anti-inflammatory properties. Hence, there is the potential role of the drug in the management of unexplained chronic cough. However, clinical trials for examining its antitussive efficacy are pivotal. In conclusion, selective PDE4 inhibitors may be potential treatments of chronic respiratory diseases apart from COPD due to their promising mechanisms of action.